Study of TiO2/Ti4O7 photo-anodes inserted in an activated carbon packed bed cathode: Towards the development of 3D-type photo-electro-Fenton reactors for water treatment. (20th April 2020) - Becerril-Estrada, V.; Robles, I.; Martínez-Sánchez, C.; Godínez, Luis A.
Abstract: In this work, commercially available Polymethyl-meta-acrylate (PMMA) spectroscopy cells were modified on the external walls with films of TiO2, Ti4 O7 or TiO2 /Ti4 O7 mixtures. Film characterization was carried out using SEM and UV–vis spectroscopy. The results of photocatalytic (PC), electro-oxidation (EO), and photoelectrochemical (PEC) experiments on the decolorization of a methyl orange (MO) model dye solution showed that while anatase provides better photocatalytic properties and the partially reduced Ti4 O7 larger electronic conductivity, the TiO2 /Ti4 O7 composite film behaves as a semiconductor substrate that combines the advantages of both materials (for PEC experiments for instance, decolorization values for the model dye solution using TiO2, Ti4 O7 and a TiO2 /Ti4 O7 mixed film, corresponded to 35%, 46% and 53%, respectively). In order to test this film as an effective photoanode material in a 3-D type reactor for water treatment processes, a TiO2 /Ti4 O7 modified PMMA spectroscopy cell was inserted in an activated carbon (AC) bed so that the semiconductor material could be illuminated using an external UV source positioned inside the PMMA cell. The connected AC particles that were previously saturated with MO dye were used as cathode sites for the oxygen reduction reaction so that the photoelectrochemical reactions that take place in the anode could be complemented with coupled electro-Fenton processes in the cathode. As expected, the combination resulted in an effective decolorization of the dye solution that results from a complex combination of processes. The experimental decolorization data was successfully fitted to a pseudo-first order kinetic model so that a deeper understanding of the contribution of each process in the reactor could be obtained. Graphical abstract: Image 1